Perhitungan Volume Overburden Weekly Pada Pit 72 Menggunakan Sofware Surpac 6.3 di PT Unirich Mega Persada Kecamatan Teweh Baru Kabupaten Barito Utara Provinsi Kalimantan Tengah - Idah Ariyaini; Suratno; Roby Cahyadi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Coal mining in Indonesia generally employs an open-pit mining system, where overburden—consisting of soil or rock layers that cover the coal seam—must be removed first. In the coal mining process, there are several layers of earth: the first layer includes topsoil and subsoil, the second consists of sand and overburden, and the final layer is coal. Overburden is considered a non-valuable material that must be excavated from the pit in order to access and extract the coal. This research aims to calculate the weekly volume of overburden in Pit 72 using RTK (Real Time Kinematic) equipment and Surpac 6.3 software. Weekly surveys were conducted to collect coordinate data (X, Y, Z), which were then processed in Surpac 6.3 to generate volume area calculations. The results show variations in the overburden volume moved each week, with a total area of 181,903.00 m² and a total overburden volume of 351,141.00 BCM over one month of observation. When compared to the monthly overburden production target of 375,000.00 BCM, the actual realization falls short. Weather conditions, haul road quality, and equipment efficiency are the main factors affecting production performance. This study demonstrates that the use of RTK and Surpac 6.3 provides more accurate and efficient measurement results compared to manual methods. This evaluation is essential for decision-making in mine progress management. Therefore, weekly volume calculations are highly valuable for monitoring production targets and enhancing the operational efficiency of the mine